Chanchada e metaficção historiográfica na construção da consciência crítica: casos de nem Sansão nem Dalila e Carlota Joaquina - Silva, Eumar Francisco da (2007)
This essay aims to establish a relationship between two parodies – Nem Sansão nem Dalila (Carlos Manga, 1954) and Carlota Joaquina, princesa do Brazil (Carla Camurati, 1995) – through the analysis of their classic and postmodern narratives, respectively. The objective is to identify how these two films built the comic discourse in order to satirize the government; at the same time this study intends to show that comedy can express political awareness and social preoccupation in a ludic way, not incompatible with the seriousness of the themes addressed. The films were chosen for corpus because of the importance attributed to them in the representation of two distinct moments of comedy in the Brazilian cinema. This essay assumes the hypothesis that, in the “critical reelaboration” (Linda Hutcheon) of Brazilian historical past, Camurati’s postmodern film strengthened the deformations already explored forty years before in a chanchada classic narrative, finding in satire and irony a metaphor of the Government’ conduct in Brazil